Anatomic extent of lymph node metastases as an independent prognosticator in node-positive major salivary gland carcinoma: A study of the US SEER database and a Chinese multicenter cohort. Issue 11 (November 2019) - Shi, Xiao; Liu, Xue-Kui; An, Chang-Ming; Wei, Wen-Jun; Tao, Yungan; Ji, Yuan; Zhang, Yan; Han, Wei; Xue, Jin-Cai; Huang, Nai-Si; Ma, Ben; Zhang, Chen-Ping; et al.
Abstract: Background: We aimed to explore whether the anatomic extent of lymph node metastases (AE-LNM) could independently predict prognosis of node-positive major salivary gland carcinoma (MaSGC). Methods: A total of 376 pathologically node-positive MaSGC patients were identified from the Surveillance, Epidemiology and End Results database and constituted the training cohort. Using the X-Tile program, these patients were divided into three groups based on AE-LNM degrees. Discrimination of overall survival (OS) and disease-specific survival (DSS) was evaluated and compared with the 8th American Joint Committee on Cancer (AJCC) pN classification. The results were externally validated by 220 patients in a Chinese multicenter cohort (Validation cohort). Results: Using the training cohort, AE-LNM was divided into Extent 1 (spread to parotid LNs or level I), Extent 2 (spread to level II-IV) and Extent 3 (spread to level V or bilateral LNs or rare LNs). Regarding both OS and DSS, the AE-LNM model revealed clear separation of survival curves, while the pN classification failed to discriminate the prognosis of pN1 and pN2 patients. When we incorporated both the AE-LNM model and AJCC pN classification into the same multivariate Cox analyses, AE-LNM was still an independent prognostic factor, while the AJCC pN classification lost its significance. These results were externally validated by the validation cohort. Conclusion: AE-LNM is an independent nodal prognosticator for node-positive MaSGC and may have improved discriminative ability over the current AJCC pN classification. Integration of anatomic extent of LNM into the current AJCC N classification could be considered.